On Gliding Hump Properties of Matrix Domains (Communications in Mathematical Research, 2021)
In this note, we establish several results concerning the gliding hump properties of matrix domains. In order to discuss $\boldsymbol{F}$-WGHP, we introduce the $\boldsymbol{U}$ $\boldsymbol{AK}$-property and find that this sort of property has close relationship with $\boldsymbol{F}$-WGHP. In the course of discussing $\boldsymbol{F}$-WGHP and WGHP of $(c_0)_{C_n}$ , we discuss the $\boldsymbol{F}$-WGHP and WGHP of the almost-null sequence space $f_0$.
Keywords: matrix domain; UAK-property; gliding hump property; sequence space